Pemerolehan Sintaksis Pada Anak Berkebutuhan Khusus Gifted: Studi Kasus Usia 8 Tahun - Nababan, Hotmida Sari (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This research aims to describe the acquisition of syntax in children with special needs gifted aged 8 years. The theory used in this research is the theory of nativism by Chomsky. The research method used is qualitative descriptive with data in the form of speeches from 8-year old gifted children obtained through methods, namely observation, interviews, and documentation. The data analysis techniques used are data analysis, data identification, categorization, and interpretation The results of the research on the acquisition of syntax in Gifted Children with Special Needs at the age of 8 years obtained the following data were obtained: (1) Acquisition of words, verbs consists of 95 data, nouns in humans consists of 9 data, nouns in objects consists of 51 data, adjectives consist of 80 data, and adverbs consist of 52 data, (2) Acquisition of phrases consists of 20 data, (3) Acquisition of clauses consists of 11 data, and (4) Acquisition of Sentences, declarative sentences (stations) consists of 15 data, interrogative sentences (questions) consist of 8 data, imperative sentences (commands) consists of 8 data. shows that the acquisition of SA syntax is quite good. The use of words, SA has been able to master word classes such as verbs, nominas, adjectives, srtya adverbs. In the use of phrases and clauses, SA is also classified as good. It's just that some words are still unclear. And the acquisition of sentences, SA is also quite good, but in the order of sentences he is often wrong in the order. From the data obtained, language acquisition based on syntatic ability in Children with Special Needs Gifted aged 8 years, namely SA, is classified in the language acquisition of children aged 4-6 years in normal children. Abstrak Penelitian ini bertujuan untuk mendeskripsikan pemerolehan sintaksis pada anak berkebutuhan khusus gifted usia 8 tahun. Teori yang digunakan pada penelitian ini yaitu teori nativisme oleh Chomsky. Metode penelitian yang digunakan ialah deskriptif kualitatif dengan data berupa ujaran-ujaran dari anak Berkebutuhan Kkusus Gifted usia 8 tahun yang didapatkan melalui cara, yakni observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan yaitu analisis data, identifikasi data, katrgorisasi, dan interpretasi. Hasil dari penelitian pemerolehan sintaksis pada Anak Berkebutuhan Khusus Gifted usia 8 tahun diperoleh data sebagai berikut: (1) Pemerolehan kata, verba terdiri 95 data, nomina pada manusia terdiri dari 9 data, nomina pada benda terdiri dari 51 data, adjektiva terdiri dari 80 data, dan adverbial terdiri dari 52 data, (2) Pemerolehan frasa terdiri dari 20 data, (3) Pemerolehan klausa terdiri dari 11 data, dan (4) Pemerolehan Kalimat, kalimat deklaratif (pernyataan) terdiri dari 15 data, kalimat interogatif (pertanyaan) terdiri dari 8 data, kalimat imperative (perintah) terdiri dari 8 data. menunjukkan bahwa pemerolehan sintaksis SA sudah cukup baik. Penggunaan kata, SA sudah dapat menguasai kelas kata seperti verba, nomina, adjektiva, srtya adverbia. Dalam penggunaan frasa dan klausa, SA juga sudah tergolong baik. Hanya saja beberapa kata masih kurang jelas pelafalannya. Dan pemerolehan kalimat, SA juga sudah cukup baik, namun pada urutan kalimat ia sering salah dalam urutannya. Dari data yang diperoleh, pemerolehan bahasa berdasarkan kemampuan sintaksis pada Anak Berkebutuhan Khusus Gifted usia 8 tahun yaitu SA tergolong dalam pemerolehan bahasa anak usia 4-6 tahun pada anak normal.